Sliding mode-based control of thin Shape Memory Alloy actuators using a spatial hysteresis approximation. (December 2016) - Kolyvas, Efthymios; Koveos, Yannis; Tzes, Anthony
Highlights: A control method for thin-Shape Memory Alloy actuators is proposed. The method is constructed by use of local approximates of hysteretic trajectories. Robustness against deviations between true and estimated temperature is shown. Robustness against delayed output feedback is demonstrated. The method is placed between model-based and model-free control for SMA actuators. Abstract: Shape Memory Alloy (SMA) actuators rely their operation on a thermally driven phase change. The SMA's stroke position control problem thus involves the material temperature in a direct or indirect way. In thin SMA actuators, deviations between the actual and the estimation of the temperature profile can affect the performance of model-based control. In this work, an intermediary strategy, between a model-free and a model-based one, is proposed, where local approximations to the hysteretic trajectories are used in place of a complete hysteresis description. The localized trajectory is then spatially shifted to encapsulate the hysteretic behavior. A sliding mode based controller is constructed by this implementation exhibiting accurate tracking behavior. The advantages against existing model-free controllers are further investigated over a multi-rate control scheme. The results show that efficient tracking position control can be reached even at very low output feedback frequencies.